APOROPHOBIA: A USEFUL AND CURRENT REFLECTION ON THE SOCIAL COM-PLEXITY OF TOMORROW - Cristina Barboza da Silva Morais, Andréia; D’arc Ferreira da Silva, Joana; Costa Rodrigues da Silva, Kênya; da Silva Farias, Roseane; Erika Ferro Ramalho Nobre, Sheila; Maria Marchi, Silvana (Revista Gênero e Interdisciplinaridade, 2024)
The contributions presented address aporophobia in contemporary Brazilian society, focusing on various dimensions of the phenomenon. The contradiction between ethical principles, proclaimed human rights and the practice of systemic rejection of poverty stands out. Aporophobia is associated with hate crimes against the poor, highlighting a conflict between the protection of individual rights and the fight against discrimination. The relationship between economic inequality, structural poverty and aporophobia is highlighted, emphasizing the importance of disseminating the debate in educational and media contexts. The urgency of confronting social inequalities is recognized, especially in the face of necropolitics exacerbated by the COVID-19 pandemic. The influence of political speeches on the culture of hate is discussed, pointing to the need for measures that promote social inclusion and the eradication of poverty. In the context of the fight against aporophobia, the importance of effective public policies stands out, aiming at social equity and guaranteeing basic human rights. In summary, the collective contributions converge towards a critical reflection on the construction of a more just, inclusive and humane society, pointing out ways to prevent and eliminate aporophobia.